2018
DOI: 10.1002/jum.14594
|View full text |Cite
|
Sign up to set email alerts
|

Influence Factors on Contrast Agent Venous Intravasation During Transvaginal 4‐Dimensional Hysterosalpingo‐Contrast Sonography

Abstract: Contrast agent intravasation during TVS 4D-HyCoSy is not infrequent. Performing TVS 4D-HyCoSy according to endometrial thickness and menstrual period could reduce intravasation incidence to some extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 13 publications
4
32
1
Order By: Relevance
“…In this study, unlike the report by Wang et al (2018), a higher venous intravasation rate occurs at 3À4 d after the menstrual cycle, not 8À9 d. In HSG, intravasation was higher during postmenstrual (3À5 d) and preovulatory (11À13 d) than during middle follicular stage (6À10 d) (Dusak et al 2013). Histopathologic studies have shown Type A = The tube was patent, and the contrast agent flowed smoothly through it.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In this study, unlike the report by Wang et al (2018), a higher venous intravasation rate occurs at 3À4 d after the menstrual cycle, not 8À9 d. In HSG, intravasation was higher during postmenstrual (3À5 d) and preovulatory (11À13 d) than during middle follicular stage (6À10 d) (Dusak et al 2013). Histopathologic studies have shown Type A = The tube was patent, and the contrast agent flowed smoothly through it.…”
Section: Discussioncontrasting
confidence: 63%
“…This phenomenon was has been referred to as "venous intravasation," which is a well-described complication during HSG and hysteroscopy (Bradley 2002;Chang and Shim 2012;Dusak et al 2013). The incidence of intravasation was 13.04%À41.3% in TV 4-D HyCoSy (Liang et al 2015;Wang et al 2018), which was much higher than that in HSG (0.4%À7.2%; Dusak et al 2013;Gowin et al 1984;Nunley et al 1987). Venous intravasation would affect the observation of fallopian tube development and pelvic cavity diffusion, leading to the difficulty in distinguishing them from intravasation.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, venous intravasation occurs in approximately 2–7% of cases undergoing HSG and seems to occur more frequently when using oil‐based contrast medium. Some reports on venous intravasation during ultrasound show a higher incidence (13%). While intravasation can potentially result in life‐threating pulmonary embolism, we are unaware of any deaths reported since the 1960s.…”
Section: Discussionmentioning
confidence: 81%
“…106 After the first report, a cascade of studies were published regarding intravasation during HyCoSy with SonoVue, showing the rate of intravasation between 13 and 26%. 107,108 It means that observers were not familiar with this event and how to recognize it earlier.…”
Section: Safety Hysterosalpingographymentioning
confidence: 99%